Performance of bitter gourd (Momordica charantia) hybrids for growth and yield attributes in the northern coastal region of Andhra Pradesh - SRINIVASULU, B; PADMA, S S VIJAYA; NAIDU, L NARAM; RAO, M PARATPARA; KUMAR, CH KIRAN (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during summer and rainy (kharif) season of 2022 at College of Horticulture, Dr. Y S R Horticultural University, Venkataramannagudem, Andhra Pradesh to find out the best performers among various parents and cross combinations for growth and yield traits in bitter gourd (Momordica charantia L.). Seven parents were maintained in a parental block (Summer, 2022) and crossed in a half diallel mating pattern in order to produce 21 F1 crosses, respectively. The crosses namely, IC-469512 × Special Boldar, IC-433630 × Special Boldar, IC-44418 × IC-469512 recorded highest vine length while IC-44418 × IC-433630 and Kashi Mayuri × IC-433630 were earlier in flowering. The hybrids, IC-44418 × IC-469512, IC-469512 × Special Boldar, IC-68314 × IC-469512 were found best for yield parameters compared to the standard checks Pragathi and Monarch. Preethi × Special Boldar shown longest fruit length and diameter whereas the hybrids IC-469512 × Special Boldar and Preethi × Special Boldar produced more number of seeds/fruit. Before being suggested for commercial release, the identified promising crosses and hybrids for earliness and yield-related traits may be further assessed in yield trials across the locations and seasons to confirm their potentiality and to determine their stability over various agro-climatic conditions.